Health Data for Linguistic Minority Group Research in Canada: Proof-of-Concept Centralized Health Care Metadata Repository Development and Usability Study - Martin-Schreiber, Vincent; Peixoto, Cayden; Batista, Ricardo; Belanger, Christopher; Tanuseputro, Peter; Hsu, Amy T; Bjerre, Lise M (JMIR Infodemiology, 2026)
Background Language barriers between Canadian patients and health care providers are associated with poorer health outcomes, including decreased patient safety and quality of care, misdiagnosis and longer treatment initiation times, and increased mortality. However, research exploring language as a social determinant of health is limited, as Canadian health data are scattered across many jurisdictions, each with its own policies and procedures. This fragmentation makes it difficult for researchers to identify, locate, and use existing data. This paper presents the results of a pilot study that attempts to address this gap by creating a metadata repository (MDR) to act as a central source of information about what data are available at which data holdings across Canada. Objective This project aimed to (1) create a proof-of-concept MDR for Canadian health data at the variable level; (2) identify and label language-related variables existing within the MDR data; and (3) develop an interactive, public-facing web application to let users browse and search the MDR. Methods Metadata were collected from 5 Canadian health data sources, including 4 provincial data holdings and 1 national survey, and pooled to create a data repository. Then, we performed bottom-up labeling of language-related variables within the pooled metadata by first using a search string algorithm across all variable labels, names, and definitions and then consensus screening these variables using a derived, standardized definition of language or linguistic variables. Using the Shiny web framework in R, we then developed an openly accessible web application to allow users to search the proof-of-concept MDR. Results A total of 850,343 variables were collected and included in the repository, with most coming from Ontario (n=712,037, 83.7%) and Manitoba (n=97,051, 11.4%) provincial data holdings. Among all variables in the repository, 213,696 (25.1%) were confirmed to be language related. Conclusions Developing a national MDR would be a transformative opportunity for Canadian researchers to leverage the full scope of Canadian health administrative data. Although a top-down approach with consistent engagement of and collaboration between provincial data holdings and federal data agencies is ideal to develop a national MDR, this study demonstrates the feasibility of a bottom-up approach in contributing to this overarching goal.

Going the distance: a cross-sectional geospatial analysis quantifying province-wide inequities in travel-based access, and fragility of access to French-language primary care provided by family physicians in Ontario, Canada - Belanger, Christopher; Timony, Patrick E; Bélizaire, Arlynn; Desilets, Antoine; Fitzsimon, Jonathan Peter; Gauthier, Alain P; Godfrey, Leanda; Karunananthan, Sathya; Kehoe MacLeod, Krystal; Muray, Mwali-Nachishali; Peixoto, Cayden; Bjerre, Lise M (BMJ Open, 2026)
Objectives Language-concordant care, or healthcare in one’s preferred language, is important both for health equity and for improving health outcomes. Linguistic minorities, like Francophones in Ontario, Canada, are at risk of poorer clinical outcomes if they receive non-language-concordant primary care. However, common ratio-based access measures can provide misleading views of minorities’ actual access levels. This cross-sectional geospatial study demonstrates a new way to measure primary care access using average travel time to the nearest five English- and French-speaking family physicians. We also introduce the concept of primary care access fragility, where a region’s primary care access may depend on one or a few local family physicians. Our research question is: are there differences in travel burden and access fragility for census subdivisions (CSDs) across language (English/French), rurality (urban/rural) and region (north/south) in the province of Ontario, Canada? Design We conducted a cross-sectional geospatial analysis to estimate English-language and French-language primary care travel burdens and access fragility in Ontario, Canada. We used population and boundary data from Statistics Canada’s 2021 census, road-network data from OpenStreetMaps, and family physician practice locations and language abilities from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Setting: We conducted our analysis for Ontario, Canada’s 577 CSDs, which correspond roughly to municipalities and with populations ranging from 5 inhabitants in Rainy Lake 17B to a high of 2 794 356 in Toronto. Participants: Using public data from January 2026, we identified 15 762 family physicians practising in Ontario, of whom 11.0% reported speaking French. Patient data were obtained from the most recent 2021 census. Primary and secondary outcome measures: Our first primary outcome measures were CSD-level mean travel time to the nearest five English-speaking family physicians, and CSD-level mean travel time to the nearest five French-speaking family physicians, which we compared to explore regional inequities in travel burden. Our secondary outcome measures were based on a novel notion of the travel burden component of ‘primary care access fragility’. This metric indicates how dependent a region’s access is on a small number of local physicians and is defined as the difference between the CSD-level mean travel time to the nearest one physician and to the nearest five physicians. As the difference in travel times grows, so too does access fragility. Results Median differences in French-language and English-language travel burdens were strongly significant across rurality, regions and overall (median difference 13.4 min, p<0.001, IQR 4.9–29.3 min), as was primary care access fragility (median difference 5.2 min, p<0.001, IQR 0.8–18.4), with larger travel burdens and fragilities in northern and rural communities. Conclusions Compared with the general public, Ontario’s French-speakers face higher travel burdens to language-concordant family physicians and higher access fragility, especially in rural and northern regions. Our results are of interest to policymakers and health-system planners, and our methods are applicable to other populations and regions.